Perancangan Tata Letak Fasilitas Gudang Komponen Perawatan Kereta LRT Jabodebek dengan Metode Class Based Storage (Studi Kasus: PT Inka) - Endrawati, Budiani Fitria; Aditia Aria Maulana; Adiek Astika Clara Sudarni (LPPM ITK, 2024)
PT Industri Kereta Api (INKA) Madiun is a railroad manufacturing company that produces trains and provides train maintenance guarantee services, one of which is to PT LRT Jakarta. The problem is that PT LRT Jakarta does not yet have a warehouse to store components for train operational and maintenance needs, so it takes time for delivery from PT. INKA Madiun to PT LRT Jakarta. This research aims to create a design and proposal for the layout of warehouse facilities in accordance with the train maintenance components at PT INKA which produces Jabodebek LRT trains. The method used is class-based storage to determine the class arrangement of each component, the rectilinear distance method to determine the distance of component movement, average speed to determine component movement time, and material handling costs to determine the total material handling cost. The results obtained show that class A is for tools components, class B is for electrical and mechanical components, and class C is for chemical, nonchemical and change unit components. The operator movement distance is 198.71 m, the forklift movement distance is 23.35 m, the operator movement time is 28,196.9 seconds, and the forklift movement time is 2,019.9 seconds for layout 1, while for layout 2 it is known that the operator movement distance is 197.60 meters, the forklift moving distance is 16.12 meters, the operator moving time is 27,889.9 seconds, and the forklift moving time is 963 seconds. The material handling costs obtained from the two layouts are Rp. 668,821,576. The layout also considers shelf dimensions, pallet dimensions, forklift dimensions, operator dimensions, door dimensions and the space of each component. The conclusion of this research is that the facility layout design is appropriate based on the class of each train maintenance component and the proposed layout chosen is layout 2 because the component movement distance and component movement time are smaller than layout 1.